Thrombotic and Hemorrhagic Complications in Patients with Mechanical Heart Valve Prosthesis Attending an Anticoagulation Clinic - Cortelazzo, S; Finazzi, G; Viero, P; Galli, M; Remuzzi, A; Parenzan, L; Barbui, T (Thrombosis and Haemostasis, 1993)
This study evaluated the advantage of an anticoagulation clinic in terms of the improvement of the clinical quality of oral anticoagulation (i.e. prevention of thromboembolism and low rate of hemorrhagic complications). The incidence of thromboembolic events and major hemorrhagic complications was assessed in a series of 271 patients on oral anticoagulation for mechanical heart valve prosthesis before and after their enrollment in our anticoagulation clinic from January 1987 to December 1990. Risk factors for hemostatic events were also analyzed. The incidence of major hemostatic complications was significantly lower when patients attended the clinic: 1.0 vs 4.9%/pt-yr for hemorrhage and 0.6 vs 6.6%/pt-yr for thrombosis. This depended on three main factors: better dose regulation of warfarin, continuous patient education and early identification of clinical conditions potentially at risk for thrombosis and hemorrhage. Only previous hemorrhagic or thromboembolic events were recognized as major risk factors for hemostatic complications.In conclusion, our study shows that an anticoagulation clinic offers a real advantage to patients with mechanical heart valve prosthesis in terms of prevention of thromboembolic events and hemorrhagic complications.